Self Efficacy Pasien Stroke di Instalasi Rawat Inap Rumah Sakit Umum Haji Surabaya - Jumain Jumain; Abu Bakar; Rachmat Hargono (FORIKES, 2020)
Stroke patients experience weakness, a negative impact that is felt to decrease self efficacy to heal resulting in lazy thoughts of activity. These beliefs greatly affect the patient's personal life including adherence to the therapy given as treatment This study aims to describe the self efficacy of stroke patients in inpatient installations. Quantitative descriptive research. The self efficacy variables of stroke patients who were temporarily admitted to the Inpatient Installation were 70 stroke patients. The research phase in the form of interviews begins on February 20 until March 20, 2019. Data obtained were analyzed using frequency distribution. Respondents with low self efficacy were 49 respondents (70.0%) and respondents with moderate self efficacy were 21 respondents (30.0%). Conclusion: for 2 months stroke patients' self efficacy obtained a low average self efficacy felt by stroke patients. Keywords: self efficacy; stroke patients ABSTRAK Pasien stroke mengalami kelemahan, dampak negatif yang dirasakan adalah menurunnya efikasi diri untuk sembuh yang mengakibatkan pikiran malas beraktifitas. Keyakinan ini sangat mempengaruhi kehidupan pribadi pasien termasuk kepatuhan terhadap terapi yang diberikan sebagai pengobatan. Penelitian ini bertujuan untuk menggambarkan efikasi diri pasien stroke di instalasi rawat inap. Penelitian deskriptif kuantitatif. Variabel self efficacy pasien stroke yang sementara waktu dirawat di Instalasi Rawat Inap adalah 70 pasien stroke. Fase penelitian dalam bentuk wawancara dimulai pada 20 Februari hingga 20 Maret 2019. Data yang diperoleh dianalisis menggunakan distribusi frekuensi. Responden dengan self efficacy rendah adalah 49 responden (70,0%) dan responden dengan self efficacy sedang adalah 21 responden (30,0%). Kesimpulan: Selama 2 bulan efikasi diri adalah rata-rata rendah yang dirasakan oleh pasien stroke. Kata kunci: self efficacy; pasien stroke